CRIMINAL LAW ENFORCEMENT AGAINST THEFT CRIMES IN NORTH TAPANULI REGENCY: A LEGAL AND CRIMINOLOGICAL ANALYSIS - Rini T Simangunsong; Motlan Gultom (Journal of International Islamic Law, Human Right and Public Policy, 2026)
Criminal law enforcement against theft is a crucial issue in maintaining order and protecting public property rights, including in North Tapanuli Regency. This study analyzes law enforcement from a juridical and criminological perspective. The discussion reveals that legal regulations are adequate, but their implementation still faces structural, social, and economic obstacles. Optimizing law enforcement requires institutional strengthening, regulatory reform, and preventive and restorative approaches. These efforts are expected to increase the effectiveness of law enforcement and create certainty and a sense of justice for the community.